2020
DOI: 10.1111/jocs.14555
|View full text |Cite
|
Sign up to set email alerts
|

Association between high dose catecholamine support and liver dysfunction following cardiac surgery

Abstract: Background Cardiac surgery using cardiopulmonary bypass is a well‐established procedure. However, up to 20% to 30% of patients require high dose vasopressor or inotropic support following surgery, enhancing the risk of organ dysfunction and impacting mortality. Nonalcoholic fatty liver disease (NAFLD) is a frequent finding in these patients and may be involved in the pathophysiology of vasoplegia and cardiac failure. Methods Retrospective analysis of 463 patients undergoing elective cardiac surgery in 2014 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…26 The use of large amounts of vasoactive drugs may be associated with an increased risk of organ dysfunction and increased postoperative in-hospital mortality. 27,28 In this trial, the utilization rate of vasoactive drugs in the high-dose sufentanil group during surgery was lower than the cohorts in other studies, which was 54.5%. This may be related to the stable hemodynamics during the operation and the low incidence of malignant arrhythmia.…”
mentioning
confidence: 50%
“…26 The use of large amounts of vasoactive drugs may be associated with an increased risk of organ dysfunction and increased postoperative in-hospital mortality. 27,28 In this trial, the utilization rate of vasoactive drugs in the high-dose sufentanil group during surgery was lower than the cohorts in other studies, which was 54.5%. This may be related to the stable hemodynamics during the operation and the low incidence of malignant arrhythmia.…”
mentioning
confidence: 50%
“…Our group has shown that NAFLD subjects undergoing major hepatic surgery frequently show impaired functional liver recovery [ 36 ]. In cardiac surgery, NAFLD is a predictor of high vasopressor support, of extrahepatic organ dysfunction, and of a longer intensive care and hospital stay [ 37 ].…”
Section: The Epidemic Of Nafldmentioning
confidence: 99%
“…In the US, metabolic fatty liver disease is currently the second leading etiology of HCC-related liver transplantation and patients undergoing major surgery have more perioperative complications and longer hospital stay. After transplantation there is a significant risk of de novo T2D and NAFLD/MAFLD, and furthermore of premature death from cardiovascular complications and sepsis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Together, MAFLD/NAFLD has to be considered a multisystem disease, as hepatic manifestation of the metabolic syndrome (MeSy)/T2D and can influence patient prognosis [ 39 , 41 , 42 ].…”
Section: Insulin Resistance As Trigger Event For Nafld Onset Progression and Clinical Coursementioning
confidence: 99%